The effect of Hegu acupoint stimulation in dental acupuncture analgesia - Fransiskus Andrianto; Jenny Sunariani; Theresia Indah Budhy S (Dental Journal (Majalah Kedokteran Gigi), 2007)
In daily life, dental treatments are often related with oral pain sensation which needs anesthesia procedures. Sometimes local anesthetics can not be used because patients have hypersensitive reaction or systemic diseases which may lead to complications. Stimulating acupoint, such as Hegu activates hypothalamus and pituitary gland to release endogenous opioid peptide substances that reduce pain sensitivity. The aim of the study was to determine Hegu acupoint stimulation effect on the pain sensitivity reduction in maxillary central incisor gingiva. The laboratory experimental research was conducted on 12 healthy male Wistar rats (3 months old, weights 150–200 grams). All rat samples received the same treatments and adapted within 1 month. The research was done in pre and post test control group design. 40-Volt electro-stimulation was done once on the maxillary central incisor gingiva prior to the bilateral Hegu acupoint stimulation, then followed by 3 times electro-stimulation with 3 minutes intervals. The pain scores were obtained based on the samples’ contraction in each electro-stimulation. The responses were categorized into 5 pain scores and statistically analyzed using Wilcoxon Test. The results showed that Hegu acupoint stimulation lowered the pain scores significantly (p < 0.05). Hegu acupoint stimulation could reduce the pain sensitivity in maxillary central incisor gingiva. Therefore, the use of acupuncture analgesia in dental pain management can be considered in the future.